Zero‐dimensional Hybrid Antimony Halide with Intrinsic Cyan Light Emission. Issue 17 (11th July 2022) - Li, Dong‐Yang; Cheng, Yu; Sun, Chuan‐Ju; Xu, Zi‐Yan; Sun, Yu‐Ming; Wang, Yu‐Jiao; Yan, Xue; Wu, Yi‐Fan; Lei, Xiao‐Wu; Yue, Cheng‐Yang
Abstract: Recently, zero‐dimensional (0D) hybrid metal halides have attracted intensive attention with wide applications in solid‐state lighting and display diodes. Herein, by using a facile wet‐chemistry method, we prepared one new 0D hybrid antimony halide of [HMHQ]2 SbCl5  ⋅ 2H2 O (MHQ=2‐methyl‐8‐hydroxyquinoline) based on the discrete [SbCl5 ] 2− unit. Remarkably, the bulk crystals of [HMHQ]2 SbCl5  ⋅ 2H2 O exhibit strong cyan light emission with a promising photoluminescence quantum yield (PLQY) of 18.92%. Systematical studies disclose that the cyan emission is mainly derived from the radiative recombination within conjugated organic cation. Benefiting from the promising luminescent performance, this 0D antimony halide can be utilized as an excellent down‐conversion light emitting luminescent material to assemble white light‐emitting diodes with high color rendering index (CRI) of 90.2. Abstract : Cyan light emitting 0D halide : To understand the specific contribution of organic component, one new 0D hybrid antimony halide of [HMHQ]2 SbCl5  ⋅ 2H2 O was rationally designed by utilizing optical active organic species as cation. This 0D hybrid halide displays intrinsic cyan light emission derived from the electron transition in organic cation with promising PLQY of 18.92%.